Implementing the Islamic Paradigm for Religious Tolerance for Peaceful Co-existence in Nigeria: The Example of Jamacat Nasrul Islam of Nigeria (JNI) - Sheu Adua, Sulaiman (Advances in Social Sciences Research Journal, 2014)
Tolerance and forgiveness are qualities which ensure success and prosperity in this world as well as in the hereafter. It should be remembered that forgiveness carries value when one is in a position to take revenge and it behaves only that person to forgive who possesses the necessary power. Islam teaches tolerance in whatever we do and if we encounter a problem or difficulty in life, we should not give up but continue struggling with prayer to God for the success of our objectives. Methodology relied solely on biographic appraisal of such studies that are related to this study. The paper looks at Jamacatul Nasril Islam in this regard by way of examining how the organisation exhibited tolerance and created avenue for peaceful co-existence among Muslims and Non-Muslims alike in all areas of its jurisdiction. The paper concludes by making few recommendations to Muslim and Non-Muslim Organisations in Nigeria to emulate the Jamacatul Nasril Islam style of operation for peaceful and harmonious co-existence in Nigeria.